Effect of an acetylene bond on hydrogen adsorption in diamond-like carbon allotropes: from first principles to atomic simulation. Issue 13 (21st March 2017) - Wu, Xuanjun; Li, Lei; Fang, Tiange; Wang, YeTong; Cai, Weiquan; Xiang, Zhonghua
Abstract : Diamond-like diacetylene theoretically exhibits exceptional gravimetric and volumetric hydrogen storage capacities due to its abundant adsorption sites. Abstract : By inserting an acetylene bond into the organic linkers of porous materials, hydrogen storage can be significantly enhanced; however, the mechanism of this enhancement remains elusive. Herein, we developed a new diamond-like carbon allotrope (referred as diamond-like diacetylene a.k.a. DDA) with medium pores constructed by inserting –CC–CC– ligands into the –C–C– bonds of diamond. The structural, mechanical, and electrical properties, as well as hydrogen storage capacities were investigated for this novel material using density functional theory and Monte Carlo simulations. The optimized geometry of DDA shows a high surface area and free pore volume of ca. 5498.76 m 2 g −1 and 2.0486 m 3 g −1, respectively. DDA also exhibits structural stability and special electronic properties. Interestingly, DDA exhibits exceptional gravimetric hydrogen storage capacity as well as volumetric one. The excess gravimetric and volumetric H2 uptakes at 77 K and 2.0 MPa hit a maximum of 14.12 wt% and 603.35 cm 3 (STP) cm −3, respectively, which substantially exceeds those previously reported for MOF or PAF materials. Even at 243 K and 12 MPa, the total gravimetric H2 uptake of DDA reaches 5.38 wt%. To the best of our knowledge, DDA is one of porous materials with the maximum physical hydrogen uptake. It is also one of the few materials that can be close to meeting hydrogen storage target of the US department of energy at room temperature. Significantly, DDA shows the deliverable hydrogen storage capacity up to 5.28 wt% at room temperature. Through analyzing the effect of the acetylene position in the DLCAs on their hydrogen storage capacities, we found that the high hydrogen adsorption performance of DDA is mainly attributed to its high surface area, large number of adsorption sites, and appropriate binding energy. In summary, the newly developed DDA is a promising candidate for hydrogen storage and provides a new possibility for synthesizing high-performance adsorbents.